2014
DOI: 10.3892/mco.2014.310
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of ultra-sensitive prostate-specific antigen following radical prostatectomy

Abstract: Abstract. This study aimed to evaluate the usefulness of ultra-sensitive prostate-specific antigen (PSA) following radical prostatectomy (RP). Between September, 2003 and March, 2009, a total of 311 prostate cancer patients underwent antegrade RP; following the exclusion of 111 patients due to prior hormonal therapy, 200 patients were finally included in this study. The results of the multivariate analysis identified RP Gleason score, extraprostatic extension, lymph node metastasis and PSA nadir as significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…An international consensus agrees that after RP, recurrent cancer may be defined by two consecutive PSA values of >0.2 ng/mL and rising . The development of ultrasensitive PSA assays have improved detection levels down to 0.008 ng/mL . The ability to detect recurrent prostate cancer in the ultrasensitive PSA range <0.2 may lead to greater interest in adoption of earlier salvage treatment.…”
Section: Introductionmentioning
confidence: 99%
“…An international consensus agrees that after RP, recurrent cancer may be defined by two consecutive PSA values of >0.2 ng/mL and rising . The development of ultrasensitive PSA assays have improved detection levels down to 0.008 ng/mL . The ability to detect recurrent prostate cancer in the ultrasensitive PSA range <0.2 may lead to greater interest in adoption of earlier salvage treatment.…”
Section: Introductionmentioning
confidence: 99%
“…One retrospective study demonstrated the usefulness of supersensitive PSA values by correlating a PSA nadir of ≤0.008 versus ≥0.008 (a value only attainable through supersensitive PSA values) with a lower probability of BCR. [ 12 ] Furthermore, the utility of BCR is restricted to measuring the outcomes of primary treatment and cannot be used to time the initiation of salvage therapies. [ 13 ] Identification of BCR as a standalone benchmark is fairly nonspecific as it does little to detail the origin of biochemical failure and the extent of disease recurrence, though some studies suggest that metastatic relapse is better predicted with a cut-point of ≥0.4 ng/mL.…”
Section: Biochemical Recurrence Definitionsmentioning
confidence: 99%
“… 6 , 7 Furthermore, ultrasensitive monitoring of PSA kinetics is an important method to identify patients requiring additional treatment. 8 …”
Section: Introductionmentioning
confidence: 99%